Biofilms in the food and beverage industries - Fratamico, Pina M. (Woodhead Publishing in food science, technology, and nutrition, 2009)
The opening chapters in this essential book consider fundamental aspects such as the ecology and characteristics of biofilms in food and beverage processing environments and methods for their detection. Part 2 then reviews biofilm formation by different microorganisms. Part 3 focuses on the significant issues of biofilm prevention and removal.